The association of TEX15 haplotype with male infertility in Vietnamese individuals - Duc Duy, La; Phuong Anh, Nguyen; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2022)
Infertility is a global concern that affects 15% of couples, and roughly half of those cases are male-specific. Among the genetic factors that contributed heavily to male infertility, TEX15 (testis-expressed gene 15) has been studied across multiple cohorts worldwide and identified to relate to meiotic recombination failure and DNA repair system malfunction. To assess the relationship between male infertility and TEX15 in a Vietnamese cohort, we performed a case-control association study of polymorphism TEX15 rs323345 and a further analysis of haplotypes of TEX15 rs323345 and TEX15 rs142485241. A total of 420 unrelated Vietnamese males, including 212 infertile patients and 208 healthy controls, were recruited for the present study. The genotype and allele frequencies of the polymorphism TEX15 rs323345 were determined by PCR-RFLP method. The results showed that the distribution of genotypes of this polymorphism followed Hardy-Weinberg equilibrium (p-value > 0.05), but the association between the polymorphism TEX15 rs323345 and male infertility was not significantly different in all three models (additive, dominant, and recessive) (p-values > 0.05). However, haplotype analysis revealed that haplotype GT of the two variants (rs323345 and rs142485241) of the TEX15 gene was correlated with an increased risk of male infertility (p = 0.023, OR = 1.937, 95% CI = 1.085-3.456). This study demonstrated that haplotype analysis could unveil potential associations in genes that could normally be unnoticed in an individual SNP analysis.